The geography of transport systems - Rodrigue, Jean-Paul (Routledge, 2017)
Revised edition of The geography of transport systems, 2013; Includes bibliographical references and index; Transportation and geography -- Transportation and the spatial structure -- Transportation, economy and society -- Transportation modes -- Transportation terminals -- International trade and freight distribution -- Urban transportation -- Transport, energy and environment -- Transport planning and policy -- Methods in transport geography -- Conclusion: issues and challenges in transport geography